Broadening out and opening up: an agonistic attitude toward progressive social accounting. Issue 2 (5th May 2015) - Dillard, Jesse; Brown, Judy
Abstract : Purpose: – The purpose of this paper is to review the current research program in agonistic dialogic accounting and to reflect on future possibilities for broadening out and opening up accounting and accountability systems, especially as they relate to social and environmental accounting (SEA). Design/methodology/approach: – The authors describe an ethic of accountability as a context for dialogue and debate intended to broaden out and open up new imaginings of accounting for democracy. The authors review the accounting literature addressing dialogic accounting and agonistics as the precursor of what has evolved into agonistic dialogic accounting. The authors discuss their work to date on agonistic pluralism and engagement, recognizing the necessity of linking the normative framework to an effective political program. The authors review prior studies applying science and technology studies that have addressed these issues. Findings: – The authors consider how the application of agonistic ideas might facilitate the development of multiple accountings that take pluralism seriously by addressing constituencies and perspectives often marginalized in both SEA and mainstream accounting. An ethic of accountability and science and technology studies are useful for stimulating dialogue and debate regarding democratic and civil society institutions as they relate to economic entities, especially corporations. Practical implications: – Agonistic dialogic accounting in conjunction with other disciplines such as science and technology studies can be used in formulating, implementing and evaluating policy for advancing a progressive social agenda. Originality/value: – A reflective view of the current work in agonistic dialogic accounting highlights considerations for further research regarding the possible interdisciplinary work particularly with science and technology studies in broadening out and opening up accounting and accountability systems as facilitators of progressive social agenda.